Control-oriented physiological modeling of hemodynamic responses to blood volume perturbation. (April 2018) - Bighamian, Ramin; Parvinian, Bahram; Scully, Christopher G.; Kramer, George; Hahn, Jin-Oh
Abstract: This paper presents a physiological model to reproduce hemodynamic responses to blood volume perturbation. The model consists of three sub-models: a control-theoretic model relating blood volume response to blood volume perturbation; a simple physics-based model relating blood volume to stroke volume and cardiac output; and a phenomenological model relating cardiac output to blood pressure. A unique characteristic of this model is its balance for simplicity and physiological transparency. Initial validity of the model was examined using experimental data collected from 11 animals. The model may serve as a viable basis for the design and evaluation of closed-loop fluid resuscitation controllers. Highlights: A model to reproduce hemodynamic responses to volume perturbation is presented. The model is equipped with balance for simplicity and physiological transparency. The model was analyzed for identifiability via parametric sensitivity analysis. Initial validity of the model was examined using data collected from 11 animals. The model will contribute to fluid resuscitation controller design and evaluation.